2017
DOI: 10.5812/ircmj.55575
|View full text |Cite
|
Sign up to set email alerts
|

Survival Analysing of the Breast Cancer Patients Using Cure Model

Abstract: Background: Breast cancer (BC) is the most leading cause of cancer and the second most common cause of cancer-related death among females worldwide. The survival time of the disease and its risk factors are important for physicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…As noted, the frailty term addition in the model did not change the direction of the effect of the covariates and at best the estimates remained the same throughout the models, and substantive conclusions from the Weibull Standard models remain valid. Consistent with findings from other studies that applied both frequentist [18,40] and Bayesian approach [36,41] separately, the presence of heterogeneity in our study acting at the region level, as determined by the two approaches, varied. Gohari et al [18] in Iran reported the frailty relative risk of 7.2 in patients with breast cancer, while Gorfine et al [42] established that accounting for heterogeneity improved the ability of the model to predict the risk of developing a disease over time based on carrier status.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…As noted, the frailty term addition in the model did not change the direction of the effect of the covariates and at best the estimates remained the same throughout the models, and substantive conclusions from the Weibull Standard models remain valid. Consistent with findings from other studies that applied both frequentist [18,40] and Bayesian approach [36,41] separately, the presence of heterogeneity in our study acting at the region level, as determined by the two approaches, varied. Gohari et al [18] in Iran reported the frailty relative risk of 7.2 in patients with breast cancer, while Gorfine et al [42] established that accounting for heterogeneity improved the ability of the model to predict the risk of developing a disease over time based on carrier status.…”
Section: Discussionsupporting
confidence: 91%
“…ough our approach is complex, the results obtained are consistent with what has been reported elsewhere. Similar to this study, metastasis increased the effects on the hazard of the event in a study conducted in Iran [40].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Many studies were made on survival of Iranian BC patients. [ 12 13 18 24 25 ] The overall relative survival in Iranian BC patients was reported higher than some Asian and eastern European countries and was lower than the U.S. and western European countries. [ 25 ]…”
Section: Discussionmentioning
confidence: 99%